2019
DOI: 10.1002/htj.21527
|View full text |Cite
|
Sign up to set email alerts
|

Second law analysis for chemically reacting natural convective second‐grade fluid flow between porous parallel plates with Hall and Ion slip

Abstract: In this article, we performed the entropy generation of free convective chemically reacting second‐grade fluid confined between parallel plates in the influence of the Hall and Ion slip with heat and mass fluxes. Let there be a periodic suction/injection along with the plates, the governing flow field equations are reduced as a set of coupled nonlinear ordinary differential equations by using appropriate similarity transformations then solved numerically with shooting method based on Runge‐Kutta 4th order sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…They observed that the rise in variable thermal conductivity reduces the fluid temperature within the channel. Some recent contributions to the topic have been made by few eminent researchers: Ramesh and Ojjela, 23 Veera Krishna, 24 Singh et al, 25,26 and Ali et al 27 In many industrial processes where the fluid is of low density or the strength of the applied magnetic field is very strong, a current is induced due to spiraling of fluid particles about magnetic lines of force, and this current is perpendicular to both the direction of applied magnetic field and motion of the fluid 28 . This current was first observed by E. H. Hall in the year 1879, and it is named as Hall current.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the rise in variable thermal conductivity reduces the fluid temperature within the channel. Some recent contributions to the topic have been made by few eminent researchers: Ramesh and Ojjela, 23 Veera Krishna, 24 Singh et al, 25,26 and Ali et al 27 In many industrial processes where the fluid is of low density or the strength of the applied magnetic field is very strong, a current is induced due to spiraling of fluid particles about magnetic lines of force, and this current is perpendicular to both the direction of applied magnetic field and motion of the fluid 28 . This current was first observed by E. H. Hall in the year 1879, and it is named as Hall current.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have implemented Walter's B fluid model to study the flow behavior of the second‐grade fluid. Some excellent papers presenting the thermal performance of viscoelastic fluids are due to Sahoo, 9 Mishra et al, 10 Rashidi et al, 11 Choudhary and Das, 12 Garg et al, 13 Singh et al, 14 Hayat et al, 15 Ramesh and Devakar et al, 16 Zhao et al, 17 and Singh et al 18 Recently, Ramesh and Ojjela 19 discussed the thermal and mass transfer behavior of second‐grade fluid within a channel with Hall and ion‐slip effects. Chen et al 20 developed a double fractional Maxwell model to explore the buoyancy‐driven flow of viscoelastic MHD fluid over a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Entropy generation minimization through heat and fluid flow in optimal design of energy systems is also an effective approach for better performance. This approach has practical importance in many applications, such as chemically reacting natural convective fluid flow, aerodynamic heating, electronic equipment cooling, solar collectors, and design of heat exchangers …”
Section: Introductionmentioning
confidence: 99%